Peran Pendidikan Kewarganegaraan Digital dalam Menghadapi Hoaks dan Disinformasi di Era Media Sosial - Agus Munandar; Muhammad Japar; Raharjo Raharjo (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The development of social media has created an open digital communication space while simultaneously increasing the spread of hoaxes and disinformation that potentially threaten social integration, democratic stability, and the quality of citizens’ participation. This study aims to analyze the role of digital citizenship education in strengthening society’s resilience against false information (hoaxes) in the era of social media. The study employs a qualitative approach using a literature review method by analyzing various national and international journals, academic books, and relevant scientific documents. The findings indicate that digital citizenship education plays a strategic role in enhancing digital literacy, critical thinking skills, digital communication ethics, and citizens’ responsibility within the virtual public sphere. The study also reveals that the low culture of information verification and the high consumption of instant information are the main factors contributing to the increasing spread of disinformation on social media. The novelty of this research lies in the development of a conceptual model of digital citizenship education based on civic resilience, which integrates digital literacy, digital ethics, and digital citizen participation as preventive measures against hoaxes. In conclusion, digital citizenship education functions not only as an instrument of democratic education but also as a mechanism for strengthening the social resilience of digital society against disinformation